Cockayne syndrome in siblings (clinico-pathological study) - Özdirim, Emire; Tınaztepe, Behçet; Pınar, Tuğrul (The Turkish Journal of Pediatrics, 1981)
Clinical and laboratory data on two siblings aged 8 years and 18 months with Cockayne syndrome are presented, the first cases reported in Turkey. Complete post-mortem examination was performed on the older sibling. Pathologic examination of the brain supports the concept that Cockayne syndrome is a form of sudanophilic leukodystrophy. Although histologic renal lesions were found, the patient presented no clinical symptoms or signs related to the kidney. The significance of the kidney histology remained obscure.